Tuning charge and correlation effects for a single molecule on a graphene device - Wickenburg,S; Lu,J; Lischner,J; Tsai,HZ; Omrani,AA; Riss,A; Karrasch,C; Bradley,A; Jung,HS; Khajeh,R; Wong,D; Watanabe,K; et al. (Nature Communications, 2017)
The ability to understand and control the electronic properties of individual molecules in a device environment is crucial for developing future technologies at the nanometer scale and below. Achieving this, however, requires the creation of three-terminal devices that allow single molecules to be both gated and imaged at the atomic scale, a difficult challenge. We have accomplished this by integrating a field effect transistor (FET) with a scanning tunneling microscope (STM), thus enabling isolated molecules on a graphene surface to be electrostatically gated and spectroscopically interrogated. Using this technique we demonstrate gate-controlled switching of the charge state of individual tetrafluoro-tetracyanoquinodimethane (F4TCNQ) molecules at the surface of a graphene FET. We observe a non-rigid shift in the F4TCNQ lowest unoccupied molecular orbital (LUMO) energy relative to the Dirac point as a function of gate voltage. This can be explained by gate-tunable graphene polarization effects that renormalize the molecular quasiparticle energies. Our results show that electron-electron interactions play an important role in how molecular energy levels align to the graphene Dirac point, and may significantly influence charge transport through individual molecules incorporated in graphene-based nanodevices.